Agon: poetry’s resistance to the mathematisation of reality (1920s-1960s) - Sridhar, A (2020)
The thesis examines the interactions between British and American poetry and mathematics, in their various forms, from the late 1920s to the 1960s. The period bears witness to an unprecedented engagement with mathematics, principally in the forms of poetic images and metaphors, ranging from responses to mathematical physics to mathematical philosophy to pure—what has recently come to be known as ‘modernist’—mathematics. The thesis investigates the complex ways in which mathematical terms function in the meaning-making procedures of poems and explores the wider intellectual and cultural forces animating the phenomenon.